Value created or destroyed in mergers and acquisitions - Goel, Avnee (2011)
In today’s global business environment, Mergers and Acquisitions (M&A) have become an important means of growth and survival for the companies. The key principle behind a merger or an acquisition is to create shareholders value since it is believed that two companies together are more valuable than two separate entities. Also these transactions help firms to expand internationally and pursue their other strategic and corporate goals.